PENGARUH KREATIVITAS KERJA, MOTIVASI KERJA DAN KOMUNIKASI EFEKTIF TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT SIMEULUE CUT KABUPATEN SIMEULUE - muhammad muhammad; Banta Karollah (SI-MEN, 2022)
This study aims to determine the effect of work creativity, work motivation and effective communication on employee performance at the Simeulue sub-district office. The sample of this study was set at 37 respondents. This result in a partial test shows that work creativity has an effect on employee performance by 0.224 or 22.4%. Likewise, work motivation has an effect on employee performance by 0.636 or 63.6%. Thus, effective communication affects employee performance 0.236 or 23.6%. After the T test shows that: 1. Work creativity affects employee performance Tcount 1.898> Ttable 1.690 and p value 0.004 < from p 0.05 means significant. 2. Work motivation has an effect on employee performance. Tcount 4,459 > ​​Ttable 1,690 with p value 0.000 from < 0.05 meaning significant. 3. Effective communication has an effect on employee performance. Tcount 2.706 > Ttable 1.690 with p value 0.003 from <0.05 meaning significant. Simultaneously there is an influence between work creativity, work motivation, effective communication and employee performance of 0.741 or 74.1% and 0.259 or 25.9% is influenced by other variables. After the F test, the Fcount > Ftable or (31.432> 3.28) and the significant test that the p value of 0.000 < p which was set at 0.05 or (0.000 <0.05) which means significant.